Mitral valve repair with the edge‐to‐edge technique: A 20 years single‐center experience. Issue 4 (29th January 2021) - Sideris, Konstantinos; Burri, Melchior; Prinzing, Anatol; Voss, Stephanie; Krane, Markus; Guenzinger, Ralf; Lange, Ruediger; Voss, Bernhard
Abstract: Objectives: For tailored treatment of primary mitral regurgitation (MR), surgeons developed different repair techniques. One of them, the edge‐to‐edge repair has recently seen a revival, especially for Barlow's disease. Methods: This study was designed to assess the outcomes of the edge‐to‐edge technique in mitral valve (MV) repair. Preoperative, periprocedural, and postoperative data were prospectively collected in a dedicated database and analyzed retrospectively. Results: Between March 1999 and July 2019, a total of 152 patients (mean age: 60 ± 13) received an edge‐to‐edge repair combined with annuloplasty for degenerative MR at our institution. MR resulted from posterior leaflet prolapse in 23 patients (15.1%), anterior leaflet prolapse in 19 (12.5%), and bileaflet prolapse in 110 (72.4%). Of those who had a bileaflet prolapse, 91 (82.7%) had Barlow's disease. Follow‐up was complete in 97.4% (6.4 ± 5.7 years). Echocardiographic assessment was achieved in 85.5% (5.1 ± 5.6 years). Overall survival after 10 years was 73.7 ± 5.0%. Twelve patients required valve‐related reoperations due to ring dehiscence ( n = 2), leaflet suture dehiscence ( n = 2), progression of native valve disease ( n = 6), or due to device failure (ring fracture) ( n = 2). The cumulative incidence of valve‐related reoperation at 10 years was 8.4 ± 3.0% (5.2 ± 4.1% in patients with Barlow's disease). At latest follow‐up, echocardiography revealed excellent valve function with no or mild MR in 93 patients (88.6%). The mean gradient was 2.9 ± 1.3 mmHg at discharge and decreased to 2.4 ± 1.3 mmHg. Three patients (2.8%) had more than moderate MR. Conclusion: Edge‐to‐edge MV repair is a simple method with excellent results in terms of valvular function and durability especially in patients with Barlow's disease.